Buckling Strength of Corroded Pipelines with Interacting Corrosion Defects: Numerical Analysis - Kuppusamy, C.S. (World Scientific Publishing Co. Pte Ltd, 2016)
Pipelines in the oil and gas industry are prone to extensive internal corrosion which leads to premature failures. Furthermore, corrosion defects within certain proximity interact to reduce the overall strength of a pipe and are termed as interacting corrosion defects. Pipelines may also experience complex loadings due to geotechnical movements such as landslides and internal pressure. Therefore, an understanding of the behavior of corroded pipelines under multiple loadings is important for the safe operation of pipelines. Extensive literature review indicates that major design codes only consider the effect of interacting corrosion defects on the burst pressure of pipes, with less attention paid to the structural behavior of steel pipes under multiple loadings. Therefore, this study focuses on the effect of interacting corrosion defects of equal depth on the local buckling strength of X46 steel pipes using the finite element analysis (FEA). Results showed that the corrosion defects interact to reduce the overall buckling strength of the pipe. Furthermore, circumferentially aligned corrosion defects are more critical than axially aligned corrosion defects, due to the greater loss of material along the circumference of the pipe. Besides, the effect of interactions of corrosion defects on the buckling strength decreases as the internal pressure increases. Lastly, as the depth of the defects increases, their interactions become more severe, which can significantly reduce the overall buckling strength of the steel pipe. Â© 2016 World Scientific Publishing Company.